Euphemism patterns in karo language at traditional marriage ceremonies - Bukit Bethesda; Erikson Saragih; Esra Perangin-angin (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
The study aims (1) to find out the patterns of euphemism in the Karo language, (2) to describe the eufemism that should be used in conversations at Karo's customary ceremonies, (3) to define the frequency of the themes of euphimism in Karo. This research approach is descriptive research with a qualitative approach. This research is based on social phenomena, i.e. descriptive data of language, analyzed in context and translated into words or sentences. The method used in this study is a descriptive method. This method is used to visualize the euphemism patterns of the Karo language in indigenous ceremonies. The method used in this study is ethnography one of the empirical and theoretical approaches that seeks for in-depth description and cultural analysis based on intensive field research. The results of the study were (1) a pattern of euphemism in the Karo language frequently found in the wedding ceremony in Karo, a marriage known as the “perjabun”,(2) a conversation on the customary ceremony of Karo’s wedding in a conversation, (3) the frequency of the theme of eufemism that exists in the language Karo that the four forms of the ceremony is the introduction of the bride there are two data with a percentage of 50%, whereas the form to the two ceremonies of flour tawar there are seven data with the percentages of 90%, the subsequent ceremony there are three data with 25%, and in the msk nasisn before-face there is one data with 25% percent.